1994
DOI: 10.1021/ac00091a044
|View full text |Cite
|
Sign up to set email alerts
|

Improved Resolution and Very High Sensitivity in MALDI TOF of Matrix Surfaces Made by Fast Evaporation

Abstract: Matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI TOF) is becoming a standard tool in mass spectrometry in general and protein analysis in particular.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
516
0
5

Year Published

1995
1995
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 683 publications
(525 citation statements)
references
References 14 publications
4
516
0
5
Order By: Relevance
“…Our experiment showed that the other two polyphenols (ECG and EGCG) possess greater antioxidant activity over GA both in the free and encapsulated state. A similar effect was observed in the DPPH assay ( Figure 12) indicating that the polyphenols with a greater number of hydroxyl groups can effectively scavenge the DPPH_ radical which is also evident from the lower EC 50 (amount of antioxidant needed to decrease the radical concentration by 50%) of ECG (4.2 6 0.1) and EGCG (3.6 6 0.0) as compared to GA (5.1 6 0.1). [80] Although the percentage inhibition values of the polyphenols are close to one another, the tread in antioxidant activity obtained from the DPPH assay is consistent with the result obtained from the DT fluorescence study.…”
Section: Docking Studiessupporting
confidence: 67%
See 1 more Smart Citation
“…Our experiment showed that the other two polyphenols (ECG and EGCG) possess greater antioxidant activity over GA both in the free and encapsulated state. A similar effect was observed in the DPPH assay ( Figure 12) indicating that the polyphenols with a greater number of hydroxyl groups can effectively scavenge the DPPH_ radical which is also evident from the lower EC 50 (amount of antioxidant needed to decrease the radical concentration by 50%) of ECG (4.2 6 0.1) and EGCG (3.6 6 0.0) as compared to GA (5.1 6 0.1). [80] Although the percentage inhibition values of the polyphenols are close to one another, the tread in antioxidant activity obtained from the DPPH assay is consistent with the result obtained from the DT fluorescence study.…”
Section: Docking Studiessupporting
confidence: 67%
“…In order of ensure the formation of RNase A dimer or higher oligomeric species, MALDI-TOF analysis [50] was performed. The matrix was pre- …”
Section: Matrix-assisted Laser Desorption Ionization-time Of Flightmentioning
confidence: 99%
“…Plasmids, recombinant protein expression, and purification excised and in-gel digested with trypsin + Three tenths of a microliter of the total digest solution was analyzed by peptide mass mapping on a Bruker REFLEX MALDI time-of-flight mass spectrometer (Bruker-Franzen, Bremen, Germany) using the fast evaporation technique for matrix preparation (Vorm et al+, 1994)+ A nonredundant protein database containing more than 300,000 entries was searched with the peptide masses+ In cases when the identification was not certain, the peptide mixture was extracted, desalted on a 100-nL Poros R2 column, eluted directly into a nano electrospray needle, and analyzed on a triple quadrupole tandem mass spectrometer (API III, PE-Sciex, Ontario, Canada; Wilm et al+, 1996)+ Proteins were identified using the sequence tag algorithm and the PeptideSearch program (Mann & Wilm, 1994)+ Tandem MS experiments were carried on a triple quadrupole mass spectrometer (API III, PE-Sciex)+…”
Section: Methodsmentioning
confidence: 99%
“…There are various types of sample preparation methods for MALDI-TOF-MS analysis, such as the drieddroplet [1], fast evaporation [33], vacuum drying [34], sandwich [35], and two-layer [36] methods. Among these techniques, the dried-droplet method is one of the most frequently used for MALDI-TOF-MS analysis in the case of solution (analyte) to solution (matrix) conditions.…”
Section: Optimizing Sample Preparation Methodsmentioning
confidence: 99%